Statement on the 2019/2020 Article of the Year: ‘Unhappy Staff, Unhappy Prisoners? The Relation Between Work Climate and Prison Climate in Dutch Prisons’ by Esther F.J.C. van Ginneken, Anouk Q. Bosma, Amanda Pasma & Hanneke Palmen (Kriminologie - Das Online-Journal | Criminology - The Online Journal, 2021)
Laudation Article of the Year